Penatalaksaan Holistik Kandidiasis Kutis Pada An. N Usia 14 Tahun Melalui Pendekatan Kedokteran Keluarga Di Puskesmas Tanjung Bintang - Rahmatika, Aufa Fitri; Arisanti, Viola; Sibuea, Sahab H. (Medula, 2023)
Candidiasis is a fungal infection caused by Candida albicans. In Indonesia, cases of cutaneous candidiasis are the third highest incidence among dermatomycosis cases. In 2013-2016, candidiasis cases were dominated by intertriginous cutaneous candidiasis at 50.5%. Internal risk factors, personal hygiene, and compliance with both medical and non-medical treatment, will greatly influence the patient's recovery. The study conducted was a case report. Data was obtained through anamnesis and physical examination by conducting home visits. The assessment is carried out based on a holistic diagnosis, process and end of visit qualitatively. Based on the examination carried out, the patient was a 14 year old girl with intertriginous candidiasis cutis. The patient's personal hygiene is not good. Patient and family knowledge about the disease is very limited. Education and intervention are provided to patients and families about candidiasis and risk factors that can trigger this disease. The internal factors in this case are the patient's lack of knowledge about the disease they are experiencing, poor personal hygiene, excessive body weight. Meanwhile, the external factors in this case were the family's lack of knowledge about candidiasis, the dominant hot weather. Pharmacological and non-pharmacological interventions are carried out by providing education regarding the causes and risk factors for candidiasis, how to use drugs, good personal hygiene, regular exercise and consumption of food with a balanced nutritional pattern. In the evaluation, it was found that there was an increase in patient and family knowledge regarding candidiasis, improvement in patient personal hygiene, and achievement of patient treatment compliance. Services with a family medicine approach in pharmacological and non-pharmacological therapy are able to solve health problems and improve the patient's quality of life.